Applying Sustainable Development in Architecture, Planning and Infra-Structure of Abha to be the First Eco-City in the Middle East - Aboneama, Wael A. (European Journal of Sustainable Development, 2018)
Sustainability improvement in Saudi Arabia and the whole Middle East is focused on only buildings and small projects. However, the history of architecture in the Middle East starting from 7th century to the end of 19th century was the real beginning of sustainable design and development. Nowadays, there is no wide planning to take a step forward towards sustainable city. Abha in Saudi Arabia could be one of the best inceptions as a sustainable city. Its climate puts Abha in the first places to be selected for applying sustainable development. Abha is the biggest city in Asir territory and the capital of tourism in Saudi Arabia. It is located 2,200 meters above the sea level with a prolific soil on the mountains of south-western Saudi Arabia (Hoiberg D. H., 2010). All over the year, the temperature moves from its lowest level around 7 C° to its maximum of 28 C° (Weather spark, n.d.). The average rainfall is 278 mm, which means that it is enough for human use and irrigation. This paper is focusing on studying the actual situation of Abha’s development and apply sustainable criteria on its architecture, planning and infra-structure to move it inside the territory of eco-cities. Keywords: Sustainable development, Abha, Architecture, Infra-structure, sustainable city